Family Harmony and Quality of Life: A Personal Relationship Approach of Gabriel Marcel in the Age of Social Media Networks - Ardi, Mohammad Noviani; Nizar, Muchamad Coirun; Maharani, Septiana Dwiputri; Menoh, Gusti A.B.; Rosyid, Abdul (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
Social media represents one of the most widely utilised platforms across the globe. This medium provides numerous conveniences for individuals to interact with one another, whether in close proximity or at a distance, among acquaintances and strangers alike. However, these conveniences do not invariably yield positive outcomes; rather, they can also entail significant disadvantages. A pressing concern is that a considerable number of cases of marital discord in Indonesia can be attributed to infidelity facilitated by social media. This study aims to assess the impact of social media usage on the quality of life and marital harmony among families in Semarang. The methodology employed in this research is quantitative, with the subjects comprising married couples residing in Semarang. Data collection was performed via a survey, utilising questionnaires administered to 131 respondents in the area. Data analysis was conducted through validity tests, reliability tests, and regression analysis employing SEM PLS software. The data was subsequently examined through the framework of Gabriel Marcel's philosophy of humanity. Marcel's philosophy is pivotal in reinstating fundamental values that define human relationships, thereby ensuring that marital connections are not merely mechanical and technocratic. This study demonstrates a significant influence of social media usage on marital harmony among families in Semarang. Consequently, collaboration among various stakeholders is essential to raise awareness regarding the paradoxes associated with social media usage. Furthermore, it is imperative to enhance couples’ understanding of the purpose of marriage and how spouses can adapt to technological advancements to ensure that family resilience remains robust. This study is positioned at a technology readiness level (TRL) of 3, involving the development of a conceptual model aimed at improving marital harmony.